Innnovation In Islamix Education Teaching and Learning In The Digital Era (Prosiding Keislaman dan Sains, 2025)
The integration of digital technology in Islamic education presents challenges and opportunities to improve the quality of learning. Although technology expands access to educational resources and increases interaction between students and teachers, challenges such as limited digital literacy, information ethics issues, and loss of personal interaction in online learning need to be addressed. This research aims to explore the challenges and innovations in implementing digital technology in Islamic education in Indonesia, as well as providing strategic recommendations for improving the quality of education. The method used is a qualitative approach with descriptive methods involving in-depth interviews, observation and documentation at Islamic educational institutions. The research results show that intensive training on digital literacy, teaching digital ethics, and strengthening personal interactions between educators and students are important steps to optimize use of technology in Islamic education. In this way, Islamic education can be transformed to become more relevant and effective in the digital era without sacrificing the values ​​of Islamic teachings.
Keywords: Digital Technology; Islamic Education; Digital Literacy; Digital Ethics; Online Learning; Personal Interaction; Educational Innovation